Synthesis, characterization, and photophysical and photochemical properties of 3-(4-phenyloxy)coumarin containing metallo- and metal-free phthalocyanines - (:unkn) unknown (My University, 2014)
0

The synthesis of novel zinc, cobalt, indium, and metal-free phthalocyanines carrying four 3-(4-phenyloxy)couma- rins in the periphery/nonperiphery were prepared by cyclotetramerization of 3-[4-(3,4-dicyanophenyloxy)phenyl]coumarin (2)/3-[4-(2,3- dicyanophenyloxy)phenyl]coumarin (3). The novel chromogenic compounds were characterized by elemen- tal analysis, 1H NMR, mass spectra, F-IR, and UV-vis spectral data. The effects of the coumarin units on the zinc, indium, and metal-free phthalocyanine complexes (2a/3a, 2c/3c, 2d/3d) were also investigated.
Keywords: Mühendislik, Kimya